(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Drug-resistant tuberculosis (DRT) is a global health issue, and changes in its laboratory parameters are crucial in assessing the course, response to treatment, and prognosis of the disease. This article provides a systematic analysis of hematological, immunological, biophysical, and molecular-genetic laboratory changes observed in PCTH. The article is compiled in IMRAD format and includes a literature review based on 12 scientific sources published over the past 5 years.